UJI EFEK ANTIINFLAMASI INFUSA BUAH SEMU JAMBU METE (Anacardium occidentale L.) TERHADAP EDEMA PADA TELAPAK KAKI TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIINDUKSI KARAGENIN - PAWESTRI, DHYNA MUTIARASARI (2010)
The Antiinflammatory Effect of Infusion of Cashew Fruit (Anacardium occidentale L) on Edema In Sole Foot of Wistar Male Rats (Rattus norvegicus) Induced by Karagenin Dhyna Mutiarasari Pawestri, EM Sutrisna, Domas Fitria Widyasari Inflammation is important mechanism to maintain the body from foreign object. Cashew fruit (Anacardium occidentale L.) has been studied for its ability as antiinflammation. This research aimed to determine the effect of cashew fruit infusion (Anacardium occidentale L.) on edema in sole foot of Wistar male rats compared with natrium diclofenac. This research was a laboratory experimental. Thirty rats (2-3 month) of 150-250 gram were used in this study and divided into 6 groups (5 rats each). Before the rats were treated, the sole foot of rats were measured by pletismometer. After 1 hours, they were injected with karagenin 0,5% 0,5ml sub plantar pedis. The edema volume in sole foot were measured every 30 minute until 300 minute. This result can be seen at AUC (Area Under Curve) expressed as mean ± SEM, the AUC0-300 was calculated and analyzed by ANOVA and continued with LSD (Least Significant Difference). The result showed that the total Area Under Curve (AUC0-300) of edema volume was 106,85 ± 0,3133 in negative control (aquadest), 65,55 ± 0,1285 in positive control (natrium diclofenac) equivalent to 6,75mg/kg BW, 94,65 ± 0,26382 in infusion of cashew fruit doses I (IBSJ I) equivalent to 1,25g/kg BW, 92,1 ± 0,1808 in IBSJ II (equivalent to 2,5g/kg BW), 102,75 ± 0,19966 in IBSJ III (equivalent to 5g/kg BW), and 110,4 ± 0,2955 in IBSJ II(equivalent to 2,5g/kg BW) + Na (equivalent to 3,375mg/kg BW). The statistical analysis showed that the AUC0-300 of IBSJ II were significantly (p<0,05) lower than those of control negative, the AUC0-300 of IBSJ I, IBSJ III and IBSJ II+Na were not significantly different (p>0,05) than those of negative control. Results of this research indicates that the infusion of cashew fruit with doses 2,5g/kg BW can degrade the edema volume in sole foot with percentage of antiinflammatory ability (%DAI) equal to 13,84%. But it was lower than positive control with %DAI equal to 38,68%. It was concluded that the infusion of cashew fruit doses 2,5g/kg BW can degrade edema volume in sole foot of Wistar male rats induced by karagenin and the reduction of edema volume was lower than natrium diclofenac.